Microbes of fermented kefir-like using combination of kefir grains and Bifidobacterium longum - Sri Usmiati; Rarah Ram (Indonesian Center for Animal Research and Development (ICARD), 2005)
The objectives of research were to find out physico-chemical characters and to detect flavor volatile compound of kefir-like. Material used was skim milk TS 9.5% which was heated at 85oC for 30 minutes and cooled at 22oC before innoculation of the starter. Microorganisms used were (a) Lactobacillus acidophilus P155110, (b) Lactobacillus delbrueckii subsp. Bulgaricus NCIMB 11778, (c) Lactococcus lactis P155610, (d) Leuconostoc mesenteroides subsp. dextranicum NCIMB 3350, (e) Acetobacter aceti P154810, (f) Bifidobacterium longum BF1, and (g) Saccharomyces cerevisiae P156252. The treatments consist of P1 = without (b); P2 = without (a); and P3= used (a) until (g). The physico-chemical characters identified were lactic acid and lactose percentages, pH, viscosity, organoleptic test for intensity of kefir-like sensory attributes. Results indicated that B. longum was potential bacterium use for starter combination on kefir-like making. The use starter P1 combination has high acidity and viscosity, low pH and lactose percentage, and high intensity on attribute creamy-white color, soft and curdle consistency, and kefir specific aroma on kefir-like. Volatile compound acid group were dominate by high acidity character on kefir-like resulted from starter P1 combination. Compound of 3-hydroxi-2-butanone (acetoin) was affecting butter-like of P3 character. This compound resulted from which is a character of fermented milk flavor was not detected on P1 kefir-like. Key Words: Fermented Milk Kefir-Like, Volatile Compound, Physicochemical Character, Bifidobacterium longum